Lecture Notes in Computer Science
DOI: 10.1007/978-3-540-78646-7_46
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility in Information Retrieval

Abstract: Abstract. This paper introduces the concept of accessibility from the field of transportation planning and adopts it within the context of Information Retrieval (IR). An analogy is drawn between the fields, which motivates the development of document accessibility measures for IR systems. Considering the accessibility of documents within a collection given an IR System provides a different perspective on the analysis and evaluation of such systems which could be used to inform the design, tuning and management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Publication Types

Select...
3
3
3

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…Retrievability was introduced to measure how likely a document is to be retrieved given an IR system [5][6][7]. Computing the retrievability scores requires the availability of a large query set, but without the need for relevance judgments.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrievability was introduced to measure how likely a document is to be retrieved given an IR system [5][6][7]. Computing the retrievability scores requires the availability of a large query set, but without the need for relevance judgments.…”
Section: Related Workmentioning
confidence: 99%
“…ing stage 5 and switch off stopword removal and stemming at indexing time (as these have already been applied in the preprocessing stage). The index granularity is the document's version d t i v .…”
Section: Preprocessing and Indexingmentioning
confidence: 99%
“…• Findability [30] • Navigability [41,21,23] • Accessibility [28,11] • Searchability [35] • Crawlability [29] • Discoverability [22] • Usability [32] • Retrievability [13] 2. What is retrievability?…”
Section: The -Abilities Of Information Retrievalmentioning
confidence: 99%
“…Retrievability is essentially a measure of the capabilities of a particular retrieval system to return documents in the collection, and retrieval bias is a measurement on the system about how the retrieval process makes certain documents more retrievable than others [4]. In prior work, it has been shown that the fairness of a system tends to correlate with retrieval performance [20], and that tuning the system via minimizing the retrieval bias may lead to improved performance [19].…”
Section: Introductionmentioning
confidence: 99%